Mitochondrial Calcium Transporters Mediate Sensitivity to Noise-Induced Losses of Hair Cells and Cochlear Synapses - Wang, Xianren; Zhu, Yuanping; Long, Haishan; Pan, Song; Xiong, Hao; Fang, Qiaojun; Hill, Kayla; Lai, Ruosha; Yuan, Hu; Sha, Su-Hua (Frontiers in Molecular Neuroscience, 2019)
Mitochondria modulate cellular calcium homeostasis by the combined action of the mitochondrial calcium uniporter (MCU), a selective calcium entry channel, and the sodium calcium exchanger (NCLX), which extrudes calcium from mitochondria. In this study, we investigated MCU and NCLX in noise-induced hearing loss (NIHL) using adult CBA/J mice and noise-induced alteration of inner hair cell synapsis in MCU knockout mice as well as modulation of mitochondrial calcium in 3T3 cells. Following noise exposure, immunoreactivity of MCU increased in cochlear sensory hair cells, while immunoreactivity of NCLX decreased in sensory hair cells in a time-dependent and exposure-dependent manner. Inhibition of MCU activity via MCU siRNA silencing or the specific pharmacological inhibitor Ru360 attenuated noise-induced loss of sensory hair cells and synaptic ribbons, wave I amplitudes, and NIHL in CBA/J mice. This protection was afforded, at least in part, through reduced cleavage of caspase 9. Furthermore, MCU knockout mice on a hybrid genetic CD1 and C57/B6 background showed resistance to noise-induced seizure as compared to wild-type littermates. Owing to the CD1 background, MCU knockouts and littermates suffer genetic higher frequencies hearing loss, but their inner hair cells are intact. Noise-induced loss of inner hair cell synaptic connections and reduction of ABR wave I amplitude were recovered in MCU knockout mice. Finally, silencing MCU in 3T3 cells decreases mitochondrial calcium concentration. These results suggest that cellular calcium influx during noise exposure leads to mitochondrial calcium overload via MCU and NCLX. Mitochondrial calcium overload, in turn, initiates cell death pathways and subsequent loss of hair cells and synaptic connections resulting in NIHL.